Does curcumin supplementation affect inflammation, blood count and serum brain-derived neurotropic factor concentration in amateur long-distance runners? - Sebastian Bańkowski; Ziemowit Bronisław Wójcik; Małgorzata Grabara; Dariusz Ozner; Tomasz Pałka; Agata Stanek; Ewa Sadowska-Krępa (PLoS ONE, 2025)
Curcumin is known for its potential health benefits; however, the evidence remains inconclusive regarding its necessity as a supplement for athletes during the preparatory phase of training. This study aimed to assess the effect of 6-week curcumin supplementation at a dose of 2g/day on selected inflammatory markers, blood count, and brain-derived neurotropic factor (BDNF) levels in middle-aged amateur long-distance runners during the preparatory period of a macrocycle. Thirty runners were randomly assigned to either a curcumin-supplemented group (CUR, n = 15) or a placebo group (PLA, n = 15). Venous blood samples were collected at rest, immediately post-exercise, and 1h post-exercise. The participants underwent a graded exercise stress test, with an increasing inclination angle after reaching a speed of 14 km/h, both before and after the 6-week supplementation period. Blood samples were collected at rest, 3 minutes post-stress test, and after 1 hour of recovery. The results showed no significant changes in C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor α (TNF-α), interleukin-1 β (IL-1β), or blood morphology due to curcumin supplementation. However, BDNF levels increased by 21% in the CUR group post-supplementation, while a 5% decrease was observed in the PLA group. These findings do not support a significant effect of curcumin supplementation on inflammatory markers, blood count, or BDNF concentration. Further research is warranted to determine the potential benefits of curcumin supplementation for endurance athletes during the preparatory period for a training cycle.